2017
DOI: 10.1016/j.plabm.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of morphological changes for the discrimination of nucleated red blood cells and other leukocytes in Sysmex XN hematology analyzer scattergrams using transmission electron microscopy

Abstract: BackgroundThe WNR channel of the XN-Series automated hematology analyzer (Sysmex) counts white blood cells (WBCs) and simultaneously performs a differential counting of basophils and nucleated red blood cells (NRBCs). The detection process involves exposing the cells to WNR-specific reagents containing an acidic detergent and a fluorescent dye and measuring the intensity of the forward scattered light (FSC) and side fluorescence light (SFL).MethodWe treated isolated peripheral WBCs and NRBCs with specific reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The anticoagulants Heparin and EDTA-2K are commonly used during blood collection for blood cell analysis [ 19 ]. We investigated whether there were differences in the measured values of %Teff, %Treg, and K-index using the WB method depending on whether heparin or EDTA-2K was used.…”
Section: Resultsmentioning
confidence: 99%
“…The anticoagulants Heparin and EDTA-2K are commonly used during blood collection for blood cell analysis [ 19 ]. We investigated whether there were differences in the measured values of %Teff, %Treg, and K-index using the WB method depending on whether heparin or EDTA-2K was used.…”
Section: Resultsmentioning
confidence: 99%
“…The NRBC count used in this study was reported as a percentage (%NRBC). NRBC detection in the WNR channel was performed on the Sysmex XN10 hematology analyzer (Sysmex Corporation) by the fluorescent flow cytometric technology using the acidic buffer and polymethine dye, accompanied with optical light scatter detection, which is claimed to reduce interference from lipids and lyse‐resistant red blood cells 19 . Approximately 9530 events per sample are counted, allowing for the lower limit of detection of 0.1% or 0.02 × 10 9 /L as reported by Da Rin G et al 14,20 The hemoglobin levels and WBC count were also collected for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Sysmex XN-3000 analyzes NRBC in a common WBC & NRBC (WNR) channel using two reagents: Lysercell WNR haemolysing reagent & Fluorocell WNR Nucleic acid dye. 10 Further analysis involves flow cytometric measurements of side fluorescence and forward scatter. Side fluorescence identifies NRBCs by measuring nucleic acid content, while, forward scatter analyses cell size.…”
Section: Methodsmentioning
confidence: 99%